LIFE SATISFACTION OF PREGNANT WOMEN IN THE CONTEXT OF INVOLVEMENT IN TAPOVAN CENTRE OF CHILDREN’S UNIVERSITY - Prajapati, A. N.; Thaker, Vrunda K (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Purpose: The purpose of the present research was to study the life satisfaction of pregnant women in terms of involvement and area in the Tapovan center. Methods: This research was an ex-post facto type of research. A non-probability’s purposive sampling method was used to select 360 people. Collection of data was carried out with the help of Life Satisfaction scale. The research tool for Life Satisfaction was developed by Promila Singh & George Joseph and Gujarati version of scale was developed and standardization by A. N. Prajapati and V. K. Thaker. In Present study Gujarati version of tool was used for collecting data. For analysis of data ‘F – Test’ was used. Finding: The finding of the study showed that there was a significant difference of Life Satisfaction in the context of involved and not involved pregnant women in Tapovan center. In which the life satisfaction of pregnant women involved in the Tapovan Center was found to be higher than that of not involved pregnant women. which proves that the activities performed at Tapovan Center have significant effects on life satisfaction of pregnant women.